Pengembangan Media Imajinopoli Sebagai Sarana Kreativitas dalam Penulisan Cerita Pendek - Zalwa Ayu Sabilah; Aida Sumardi (Jurnal Membaca (Bahasa dan Sastra Indonesia), 2026)
This study was conducted to develop imaginopoly media as an alternative that can encourage students' creativity in writing short stories at the junior high school level. This media is expected to provide a more interesting and interactive learning experience, as well as motivate students to explore ideas more freely, so that the writing process is no longer considered challenging or boring. The purpose of this study is to evaluate the effectiveness of the imaginopoli media in improving short story writing skills and to determine the extent to which this media contributes positively to the development of students' writing skills. The method applied in this study was Research and Development (RND) using the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation, so that the development process was carried out systematically and in accordance with learning needs. The results of the validation test showed that the imaginopoly media was categorized as good, with an average score of 94.6% from media experts and 81.4% from subject matter experts. In addition, the student response test also showed very satisfactory results, with small classes obtaining an average score of 90.2% and large classes 89.3%. The response from teachers, who are important supporters in the teaching and learning process, also showed positive results with an average score of 84%. Overall, the results of this study confirm that the imaginopoly media meets